Planetary systems beyond the main sequence: proceedings of the International Conference "Planetary Systems beyond the Main Sequence", Bamberg, Germany, 11 - 14 August 2010 - Schuh, Sonja; Drechsel, Horst (AIP conference proceedings, 2011)
"Fields: Astrophysicists working on extrasolar planets, white dwarfs, giant stars, pulsars, astrobiology. This conference was the first to discuss the fate of a planet and its host star when the star evolves into a red giant and finally ends its life as a white dwarf. Scientists specialised in stellar evolution met experts from the exoplanet field to discuss this interplay"--Publisher's Web site
Sponsoring organizations: German Science Foundation DFG
Erscheinungsjahr in Vorlageform:2011
Keywords: Konferenzschrift; Extrasolarer Planet